Field‐programmable lab‐on‐a‐chip based on microelectrode dot array architecture. Issue 3 (1st September 2014) - Wang, Gary; Teng, Daniel; Lai, Yi‐Tse; Lu, Yi‐Wen; Ho, Yingchieh; Lee, Chen‐Yi
Abstract : The fundamentals of electrowetting‐on‐dielectric (EWOD) digital microfluidics are very strong: advantageous capability in the manipulation of fluids, small test volumes, precise dynamic control and detection, and microscale systems. These advantages are very important for future biochip developments, but the development of EWOD microfluidics has been hindered by the absence of: integrated detector technology, standard commercial components, on‐chip sample preparation, standard manufacturing technology and end‐to‐end system integration. A field‐programmable lab‐on‐a‐chip (FPLOC) system based on microelectrode dot array (MEDA) architecture is presented in this research. The MEDA architecture proposes a standard EWOD microfluidic component called 'microelectrode cell', which can be dynamically configured into microfluidic components to perform microfluidic operations of the biochip. A proof‐of‐concept prototype FPLOC, containing a 30 × 30 MEDA, was developed by using generic integrated circuits computer aided design tools, and it was manufactured with standard low‐voltage complementary metal‐oxide‐semiconductor technology, which allows smooth on‐chip integration of microfluidics and microelectronics. By integrating 900 droplet detection circuits into microelectrode cells, the FPLOC has achieved large‐scale integration of microfluidics and microelectronics. Compared to the full‐custom and bottom‐up design methods, the FPLOC provides hierarchical top–down design approach, field‐programmability and dynamic manipulations of droplets for advanced microfluidic operations.